Vocabulary development of EFL young learner after long peer interaction with video games - Asari, Slamet (Universitas Muhammadiyah Sidoarjo, 2023)
The development of online games nowadays is not only for the purpose of entertaining but it can also be for English learning purpose since English language is commonly used as a language of instruction there in the games. Many researchers have developed online games on language use, one of which is English that focuses on vocabulary development and communicative language functions. This present study aims to find out or investigate the interactions and vocabularies learned by EFL learner while playing video games. The design of this research was a case study with a high school student. The data was taken from observation, videotaping peer interactions and depth interviews. The result indicated that he interacted not only with games but also with friends or teachers in English classrooms in gaining vocabulary (incidental vocabulary learning). The interaction occurred incidentally where they learned new vocabulary from interaction with video games and expressively used them in realistic situations. The data analysis relieved different words EFL Students learned from video games interaction as good as vocabulary gains. It included vocabulary support and learning patterns, spontaneous vocabulary interaction, and vocabulary improvement in video games interaction skill. As a result, this research found a potential theory that was implemented unconsciously in the observation of activities. This research can be used as a way for both teacher and student to optimize vocabulary development. HIGHLIGHTS: EFL students interacted in an incidental manner in which they learned new vocabulary through interaction with video games and expressively used it in realistic situations. The supports from peer did not appear in every interaction episode because they occurred incidentally within the real flow of the engagement and because the goal of such spontaneous talks was not to teach him the language meanings. Subject was more likely to pick up and use specific word in future scenarios with other peers. He engaged in self-regulated learning unconsciously.